BURNOUT AMONG POSTGRADUATE RESIDENTS USING COPENHAGEN BURNOUT INVENTORY - Majeed, Fatima; Naeem Liaqat; Maqbool Hussain, Mian; Iqbal, Asif; Hashim, Imran; Saleem, Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Generally, the healthcare workers have a stressful job and it includes both physical and mental stress. We conducted this study to determine the burnout among postgraduate residents (PGR’s). Methods: This cross-sectional study was conducted at The Children’s Hospital and The Institute of Child’s Health, Lahore over a period of 3 months. A total of 113 PGR’s participated in this study. Burnout was measured using Copenhagen Burnout Inventory (CBI). Questionnaire was filled by participants on paper. Results were analyzed through SPSS-26. Results: In this study, most of the participants (n=70) were females. Mean age of the participants was 28.6±2.035 years. More than 50% participants suffer from moderate to severe burnout. Nine percent of participants had high personal and client related burnout. The highest mean score was for personal burnout scale. When burnout scores were categorized according to demographic details, personal burnout was significantly higher among those who considered that they are burnout (p=0.000) and work burnout was significantly higher among those who travelled to the workplace by their cars (p=0.025). Burnout was higher among females, those who have long duration to travel from their homes to the hospital and whose parents were doctors; however, the difference was not significant. The scale showed a good overall internal reliability (Cronbach’s alpha=0.697). Conclusion: This study showed a high rate of burnout among PGR’s that needs to be addressed and adequate measures should be taken to reduce it.